2011
DOI: 10.1073/pnas.1111825108
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal seasonal variation in vitamin D status and tuberculosis notifications in Cape Town, South Africa

Abstract: Vitamin D deficiency is associated with susceptibility to tuberculosis (TB) in HIV-uninfected people in Europe, but it is not known whether such an association exists among HIV-infected people in subtropical Africa. We conducted a cross-sectional study to determine whether vitamin D deficiency was associated with susceptibility to active TB in and HIV-infected (n = 174) black Africans in Cape Town, South Africa. We also investigated whether there was evidence of seasonal variation in vitamin D status and TB n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
182
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(222 citation statements)
references
References 33 publications
34
182
6
Order By: Relevance
“…Martineau et al (1) found that there is a significant association of vitamin D deficiency with susceptibility to TB and that the impact is greater in HIV-infected than noninfected individuals. In addition, Martineau et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Martineau et al (1) found that there is a significant association of vitamin D deficiency with susceptibility to TB and that the impact is greater in HIV-infected than noninfected individuals. In addition, Martineau et al…”
mentioning
confidence: 99%
“…T he paper in PNAS by Martineau et al (1) raises a key public health issue: how much vitamin D do you need to fight tuberculosis (TB)? Martineau et al (1) found that there is a significant association of vitamin D deficiency with susceptibility to TB and that the impact is greater in HIV-infected than noninfected individuals.…”
mentioning
confidence: 99%
“…It is not self-evident, though, that these results can be transferred to HIV-infected subjects: for patients on anticonvulsant drugs (which are considered to interfere similarly to ART [1]) and patients with hyperparathyroidism (which was found to occur secondary to ART with tenofovir disoproxil fumarate [5,6]) a loss of seasonality has been described [7,8]. Although a seasonal difference has been hinted at in some small or highly selective HIV-infected populations [9][10][11][12], detailed information is sparse. Yet, knowledge about seasonality is essential for interpretation of laboratory results of vitamin D concentrations.…”
Section: Seasonal Variations In Vitamin D Levels In Hiv-infected Patimentioning
confidence: 99%
“…2 Vitamin D deficiency, for example, was reported in 2011 to be extremely common in black Africans living in Cape Town, and it was associated with susceptibility to tuberculosis (TB) infection. 3 It was concluded that vitamin D supplementation may be a highly cost-effective, safe and simple means to reduce TB incidence. 3 In a study recently reported by Busse et al, 4 the negative impact of vitamin D deficiency on bone health, specifically the higher risk for bone fractures was demonstrated; however, its impact on other health areas is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…3 It was concluded that vitamin D supplementation may be a highly cost-effective, safe and simple means to reduce TB incidence. 3 In a study recently reported by Busse et al, 4 the negative impact of vitamin D deficiency on bone health, specifically the higher risk for bone fractures was demonstrated; however, its impact on other health areas is less clear. Vitamin D deficiency has been suggested, for example, to play a role in depression 5 and has also been associated with increased HIV-1 replication in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%